1991
DOI: 10.12935/jvma1951.44.319
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Blood Biochemical Findings on Uric Acid Lithiasis of the Urinary Tract in Newborn Piglets

Abstract: With the objective of elucidating the etiology of uric acid calculi of the urinary tract in newborn piglets, 28 healthy newborn piglets and 21 weak newborn piglets, which were born in the winter months, were investigated.Clinically, yellow diarrhea was observed in 10 of the weak newborn piglets. Autopsy of these piglets revealed pale pink, fine granular calculi in the renal pyramids and papillae in 8 piglets, and abnormalities, such as petechial hemorrhage and edema in the kidneys, as well as discoloration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1992
1992
1998
1998

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…These diseases are ascribed to extraordinary activities of the enzymes, and they are manifested as uricemia, uricosuria and uric acid stones. There are a few studies dealing with xanthine oxidase and uricase in newborn piglets [7,8]. In swine, hypoxanthine and xanthine are metabolized to uric acid by xanthine oxidase, and the uric acid is metabolized to allantoin by uricase [2,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These diseases are ascribed to extraordinary activities of the enzymes, and they are manifested as uricemia, uricosuria and uric acid stones. There are a few studies dealing with xanthine oxidase and uricase in newborn piglets [7,8]. In swine, hypoxanthine and xanthine are metabolized to uric acid by xanthine oxidase, and the uric acid is metabolized to allantoin by uricase [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several clinical investigations of this disease [6,8,17] since Madsen et al [11] made the first report of clinical cases in 1944. Although these studies have suggested, as predisposing factors for this disease, viral infection [6], a low level of uricase activity in the liver [7,11], colds [7], starvation [11] and an excess of purine metabolism [8], the determinable etiology has not been demonstrated. We previously investigated the incidence of the uric acid stones in the kidneys of the newborn piglets at necropsy [9], and found that 108 of 1,338 piglets died within 18 days of age and uric acid stones were present in 13.0% of the dead piglets mostly with low body weight.…”
mentioning
confidence: 99%
“…Nach neueren Berichten starben 230 von 1100 lebend geborenen Ferkeln in den ersten 2-19 Tagen (MAHANTA u. CHAUDHURY, 1988), 60 davon wiesen Harnsauresedimente in den Harnwegen auf, das sind 26,08 % aller Todesfalle. Nach anderen Beobachtungen (KAKINO et al, 1991) waren bei 8 von 21 an allgemeiner Schwache gestorbenen Ferkeln Harnsaureabscheidungen in den Nierentubuli festzustellen.…”
unclassified